2016
DOI: 10.1145/2980179.2980225
|View full text |Cite
|
Sign up to set email alerts
|

Automated view and path planning for scalable multi-object 3D scanning

Abstract: Demand for high-volume 3D scanning of real objects is rapidly growing in a wide range of applications, including online retailing, quality-control for manufacturing, stop motion capture for 3D animation, and archaeological documentation and reconstruction. Although mature technologies exist for high-fidelity 3D model acquisition, deploying them at scale continues to require non-trivial manual labor. We describe a system that allows non-expert users to scan large numbers of physical objects within a reasonable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Our system highlights the boundaries of the reconstructed model after each scan is integrated (Figure 12, left), suggesting where data is required and helping to plan the next scan. While more advanced next-best-view optimizations could be integrated [Fan et al 2016;Wu et al 2014], we found the guidance provided by our direct visual feedback to be sufficient for all our experiments. We efficiently scanned models with complex shapes, combining an initial set of automatic scans (taken using a rotational stage), with a few manual scans of the occluded regions (Figure 12, right).…”
Section: Resultsmentioning
confidence: 97%
“…Our system highlights the boundaries of the reconstructed model after each scan is integrated (Figure 12, left), suggesting where data is required and helping to plan the next scan. While more advanced next-best-view optimizations could be integrated [Fan et al 2016;Wu et al 2014], we found the guidance provided by our direct visual feedback to be sufficient for all our experiments. We efficiently scanned models with complex shapes, combining an initial set of automatic scans (taken using a rotational stage), with a few manual scans of the occluded regions (Figure 12, right).…”
Section: Resultsmentioning
confidence: 97%
“…Some works (e.g. (Fan et al, 2016;Ahmadabadian et al, 2014a,b;Trummer et al, 2010)) thus focus on the reconstruction of small scale scenes in laboratories. For this kind of approaches we refer the reader to a recent review article of Karaszewski et al (2016).…”
Section: Related Workmentioning
confidence: 99%
“…Reinforcement learning has been utilized to estimate camera trajectories for scene exploration [Kollar and Roy 2008), but not for quality 3D reconstruction. For scanning multiple objects, Fan et al [2016] select the best views for each object and then optimize the entire scanning trajectory by solving a Traveling Salesman Problem, with a special scanning setup. lt is, however, unclear how this method could be extended to a mobile robot setting which requires collision avoidance.…”
Section: Related Workmentioning
confidence: 99%